Bridge Enhanced ACL Repair Throughout Varied Patient Populations: Clinical Outcomes, Patient Priorities, and Equity Focused Research Gaps - Weng, Kai-Chiun; Alansi, Abdulrahman; Kravets, Alesia; Bessmylna, Kateryna; Zhukava, Lizaveta; Chrobak, Agata; Volkawa, Darya; Sakovich, Volha; Kacynel, Ewa; Myślicka, Wiktoria (Quality in Sport, 2026)
Background. Bridge-enhanced anterior cruciate ligament repair (BEAR) alternative to ACL reconstruction Interest has grown due to its ability to maintain tissue continuity, preserve hamstring strength, and support faster recovery. However, evidence of its effectiveness across diverse patient populations remains limited. Aim. Integrate current evidence on clinical outcomes, patient-centered benefits, safety, and equity-related research gaps associated with BEAR in varied patient groups and clinical settings. Material and methods. This review includes evidence from randomized clinical trials, first-in-human cohort studies, registry data, post-market observational studies, case reports, surgical technique publications, and patient preference research. Results. Early real-world data suggest good short-term safety and functional outcomes across broader adult groups, including women and middle-aged patients. However, evidence remains concentrated in young, active populations, with limited subgroup analyses and insufficient long-term data in older or non-elite patients. Conclusions. BEAR is a promising alternative to standard ACL reconstruction for selected patients with acute ACL tears, offering comparable stability and function with better muscle preservation and faster early recovery. Larger, long-term, and more inclusive studies are still needed to clarify its role across diverse patient populations and support individualized clinical decision-making.